Penyuluhan Pembuatan Yogurt sebagai Makanan Sehat pada Ibu-Ibu Majelis Ta’lim di Kelurahan Kukusan, Kecamatan Beji, Kota Depok - Emilda Emilda; Rosa Dewi Pratiwi (Universitas Indraprasta PGRI, 2022)
Dairy consumption in Indonesia is still low compared to other countries. One way to increase it by dairy processing into other forms such as yogurt. Yogurt has high nutritional and health benefits. Therefore, this yogurt-making counseling activity was carried out to increase the consumption of healthy food for the community, especially those made from dairy. The purpose of this activity is to improve people knowledge about its benefits and provide new skills to make their own yogurt that is more affordable and preferred. The target of the activity was the members of the Khotmul Qur-an Ta'lim Council and MT Yaumul Jumuah RT 03 RW 03 in Kukusan Village, Beji District, Depok. Based on the counseling activities showed that the participants were enthusiastic about the counseling held because it provided new knowledge and skills. And participants also understood the benefits and how to make yogurt at home as an alternative to healthy food.